SOME THEORIES ON LANGUAGE REVITALIZATION - Masruddin Masruddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2015)
One of the focuses of the linguistic world nowadays is language shift phenomenon. Many different approaches dealing with language maintenance and shift can be found in the literature on minority languages. All weight the importance of the various factors influencing language maintenance differently. Their importance differs according to the situation in which a linguistic minority lives. This paper tries to describe some theories on revitalizing the languages which are in endangered situation. Some theories give consideration about how to save the languages.